2021
DOI: 10.1039/d1ra06338c
|View full text |Cite
|
Sign up to set email alerts
|

Natural deep eutectic solvents as tailored and sustainable media for the extraction of five compounds from compound liquorice tablets and their comparison with conventional organic solvents

Abstract: A 1,4-butanediol–levulinic acid system was selected as a topgallant solvent and extraction parameters were optimized. NADES extracts exhibited higher extraction efficiency and in vitro antioxidant activities than conventional solvent extracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The DES extract scavenging rate was higher than the other three extracts, and experiments by Dong showed that this showed a dose relationship with its saponin-containing concentration and indicated that it has some antioxidant capacity and can be used to delay or limit lipid oxidation. 6 …”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The DES extract scavenging rate was higher than the other three extracts, and experiments by Dong showed that this showed a dose relationship with its saponin-containing concentration and indicated that it has some antioxidant capacity and can be used to delay or limit lipid oxidation. 6 …”
Section: Results and Analysismentioning
confidence: 99%
“…The DES extract scavenging rate was higher than the other three extracts, and experiments by Dong showed that this showed a dose relationship with its saponincontaining concentration and indicated that it has some antioxidant capacity and can be used to delay or limit lipid oxidation. 6 3.9.2 Analysis of the results of the chelating rate of iron ions. The ability to chelate ferrous ions is one of the commonly used methods to assess the antioxidant activity of a subject.…”
Section: Des Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…246−249 The application of organic solvents in the extraction processes comes with some disadvantages, such as high flammability, high vapor pressure, and, in some cases, toxicity. 250,251 Additionally, some extracted compounds, e.g., anthocyanins, are prone to degradation at high temperatures. Thus, it is even more difficult to efficiently extract them with organic solvents.…”
Section: The Most Interesting Bioactive Compounds Extracted With Dess...mentioning
confidence: 99%
“…Traditional methods of extraction include Soxhlet extraction with solvents such as ethanol, methanol, and acetone and extraction with the aid of stirring and heating, commonly used together with the assistance of ultrasound or microwaves. The application of organic solvents in the extraction processes comes with some disadvantages, such as high flammability, high vapor pressure, and, in some cases, toxicity. , Additionally, some extracted compounds, e.g., anthocyanins, are prone to degradation at high temperatures. Thus, it is even more difficult to efficiently extract them with organic solvents.…”
Section: Effect Of Type Of Des and Process Conditions For Extraction ...mentioning
confidence: 99%